Oxynoemacheilus karunensis, a new species from the Persian Gulf basin Teleostei: Nemacheilidae) - Freyhof, Jörg (Zootaxa, 2016)
Nemacheilid loaches of the genus Oxynoemacheilus are common fishes all over the Middle East (Freyhof et al. 2011). From Iran, Jouladeh-Roudbar et al. (2015) recognised 12 species from Iran (O. angorae (Steindachner), O. araxensis (Bănărescu & Nalbant), O. bergianus (Derjavin), O. brandtii (Kessler), O. chomanicus (Kamangar, Prokofiev, Ghaderi & Nalbant), O. frenatus (Heckel), O. kermanshahensis (Bănărescu & Nalbant), O. kiabii (Golzarianpour, Abdoli & Freyhof), O. kurdistanicus (Kamangar, Prokofiev, Ghaderi & Nalban)t, O. persa (Heckel), O. tongiorgii (Nalbant & Bianco), O. zagrosensis (Kamangar, Prokofiev, Ghaderi & Nalbant). From these, O. angorae (endemic to the western and Central Anatolian Black Sea basin), O. araxensis (endemic to the uppermost Euphrates drainage) and O. frenatus (endemic to the upper Tigris drainage) have never been confirmed from the territory of Iran and are unlikely to be found there in the future. Oxynoemacheilus kermanshahensis has recently been transferred to the genus Sasanidus (Freyhof et al. 2016). From the remaining eight Iranian species listed by Jouladeh-Roudbar et al. (2015), O. brandtii is found in the Kura and Arax River drainages and in the Lake Urmia basin, O. persa is known from the Mond River drainage and the endorheic Kor River drainage and O. tongiorgii is endemic to the Kor River drainage. Five species occur in the Tigris drainage (O. bergianus, O. chomanicus, O. kiabii, O. kurdistanicus and O. zagrozensis) and O. bergianus is much more widespread in Iran, the Caucasus and Turkey. Freyhof et al. (2016) transferred Ilamnoemacheilus longipinnis, from the Tigris drainage, to Oxynoemacheilus raising the number is Iranian Oxynoemacheilus species to nine.